Tangshen Formula Attenuates Diabetic Nephropathy by Promoting ABCA1-Mediated Renal Cholesterol Efflux in db/db Mice - Liu, Peng; Peng, Liang; Zhang, Haojun; Tang, Patrick Ming-Kuen; Zhao, Tingting; Yan, Meihua; Zhao, Hailing; Huang, Xiaoru; Lan, Huiyao; Li, Ping (Frontiers in Physiology, 2018)
The commonly prescribed Tangshen Formula (TSF) is a traditional Chinese formulation that has been shown to reduce plasma lipid metabolism and proteinuria and improve the estimated glomerular filtration rate (eGFR) in patients with diabetic kidney disease. This study investigated the underlying mechanism whereby TSF regulates renal lipid accumulation and ameliorates diabetic renal injuries in spontaneous diabetic db/db mice and in vitro in sodium palmitate (PA)-stimulated and Abca1-SiRNA-transfected mouse tubular epithelial cells (mTECs). The results revealed that TSF treatment significantly ameliorated the renal injuries by lowering urinary albumin excretion and improving renal tissue injuries in diabetic (db/db) mice. Interestingly, the treatment with TSF also resulted in decreased cholesterol levels in the renal tissues of db/db mice, which was associated with increased expression of the peroxisome proliferator-activated receptor γ coactivator 1-α (PGC-1α), the Liver X receptors (LXR), and ATP-binding cassette subfamily A member 1 (ABCA1), suggesting that TSF might attenuate diabetic kidney injury via a mechanism associated with improving cholesterol efflux in the diabetic kidney. This was investigated in vitro in mTECs, and the results showed that TSF reduced the PA-stimulated cholesterol accumulation in mTECs. Mechanistically, the addition of TSF was capable of reversing PA-induced downregulation of PGC-1α, LXR, and ABCA1 expression and cholesterol accumulation in mTECs, suggesting that TSF might act the protection via the PGC-1α-LXR-ABCA1 pathway to improve the cholesterol efflux in the renal tissues of db/db mice. This was further confirmed by silencing ABCA1 to block the promotive effect of TSF on cholesterol efflux in vitro. In conclusion, TSF might ameliorate diabetic kidney injuries by promoting ABCA1-mediated renal cholesterol efflux.